Analisa dan Perancangan Pemesanan Minuman Pada Kedai Kopi Satu Arah Berbasis Web - Dimas Panji Naufaldi; Budi Apriyanto (CV. Multi Kreasi Media, 2023)
Satu Arah Coffee Shop is a shop that provides many types of coffee from various regions. Therefore, sales at the Satu Arah Coffee Shop are growing rapidly because of the large number of coffee lovers nowadays. The conventional drink ordering process is not enough to overcome the many customers who come to enjoy various kinds of coffee at the shop, because there are still many obstacles such as the lack of information on the menu list in the shop, then the transaction process still uses conventional methods such as recording in a book. So the shop owner tries to use a computerized method that makes it easier for the shop owner to make transactions. This is also to make it easier for customers to be more efficient in ordering drinks or food. The computerized system used is a Web-based Information System. This Web-based Information System is used to process transactions between shop owners and customers, can also help customers in terms of ordering coffee or food as well as information related to the menu in this shop, so as to provide convenience for customers in terms of ordering. In designing this Web-based information system using a model with Unified Modeling Language (UML) including Use Case Diagrams, sequence diagrams, Class Diagrams and Activity Diagrams. Built using the PHP, Programming language with MySql as the database.